Human Cartilage Homogenates Influence the Crystallization of Monosodium Urate and Inflammatory Response to Monosodium Urate Crystals: A Potential Link Between Osteoarthritis and Gout. Issue 12 (6th November 2019) - Chhana, Ashika; Pool, Bregina; Wei, Yicheng; Choi, Ally; Gao, Ryan; Munro, Jacob; Cornish, Jillian; Dalbeth, Nicola
Abstract : Objective: Monosodium urate (MSU) crystal deposition and gout flares frequently affect osteoarthritic joints. This study was undertaken to examine the effects of human cartilage homogenates on MSU crystallization and MSU crystal–induced inflammation. Methods: Human cartilage homogenates were prepared from macroscopically healthy and macroscopically diseased knee joint samples. Crystallization assays were used to test the effects of cartilage homogenates or individual cartilage factors on MSU crystallization. Changes in urate solubility, crystal nucleation, crystal growth, and total crystal mass were determined. THP‐1 cell assays were used to assess cytokine release following culture with MSU crystals grown in the presence or absence of cartilage homogenates or individual proteins. Results: Addition of either 5% or 10% healthy cartilage homogenate increased the total mass of MSU crystals formed and resulted in formation of shorter MSU crystals compared to controls without cartilage homogenate. MSU crystal bows were observed in both the presence and absence of cartilage homogenate; however, bows formed in the presence of cartilage homogenates were significantly shorter than bows formed in their absence. There were no effect differences between macroscopically healthy and macroscopically diseased cartilage homogenates in all assessments. Addition of either type II collagen or albumin also led to the formation of shorter MSU crystals. In THP‐1 cell assays, MSU crystals grown with healthy cartilage homogenate increased the release of interleukin‐8, whereas MSU crystals grown with type II collagen or albumin had no effect on inflammatory cytokine release. Conclusion: In the presence of elevated urate levels, human cartilage homogenates increase MSU crystal formation and promote the formation of smaller crystals, which have greater inflammatory potential. These processes may contribute to the predilection of osteoarthritic joints to develop gout.